EVALUASI KURIKULUM PENDIDIKAN ISLAM DI SEKOLAH DASAR - Nuryanti, Ika Putri; dahlan, zaini (Institut Syekh Abdul Halim Hasan Binjai, 2024)
Islamic education at the elementary level plays a crucial role in forming children's character and morals in accordance with Islamic teachings. Curriculum evaluation is an important step in ensuring the effectiveness and relevance of the curriculum to the objectives of Islamic religious education as well as the needs and social context of students. Although there has been several studies related to the evaluation of Islamic education curricula, there are still research gaps, especially in the elementary school context. Therefore, this research aims to carry out a systematic evaluation of the Islamic education curriculum at the elementary school level by paying attention to important aspects such as the success of achieving educational goals, increasing understanding and practice of Islamic teachings, as well as the relevance of the material to the needs and social context of students. A qualitative approach with a case study design was used in this research involving various research subjects such as teachers, students, parents and school administration staff. The empirical data obtained was then analyzed by considering relevant theoretical frameworks such as constructivism theory, social learning theory, and curriculum development theory. The research results show that evaluation of the Islamic education curriculum in elementary schools has a significant impact in influencing students' understanding and practice of Islamic teachings. Several suggestions for further development were also put forward, including the development of holistic evaluation methods, increased training for teachers, further research on the impact of curriculum implementation, and collaboration between educational institutions, government and religious organizations.